THE CONCEPT OF PEDAGOGICAL EDUCATION IS IMPLEMENTED IN THE FAMILY IN THE WORKS OF ABDURAUF FITRAT (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
The article analyzes the concept of pedagogical education in the family of Abdurauf Fitrat and draws methodological conclusions.